Peningkatan Kapasitas Literasi Digital dan Pembuatan Konten Pemasaran bagi Pelaku Budidaya Perikanan di Desa Sukajadi, Bogor - Syamsu Hidayat; Rino Subekti; Rahmat Jaya; Dwi Sidik Permana; Filda Angelia; Johan Bastari; Hilman Jihadi (Jurnal Abdimas: Sosial, Bisnis, dan Lingkungan, 2025)
The objective of the community service program is to enhance digital literacy and improve marketing skills for fish farming in Sukajadi Village, Bogor. This initiative aims to assist fish farmers in effectively utilizing digital media to sell their products and connect with a broader customer base. The implementation strategy involves social integration, skills development, and hands-on experience, scheduled for a full day (8 hours) on July 18, 2025. The program will engage 20 fish farmers and local micro, small, and medium enterprises (MSMEs). The approach includes using smartphones to capture photos and videos that promote fishery products. The results of the activity revealed a significant 65% increase in the digital literacy of the participants, particularly in their abilities to take pictures, edit content, and publish on social media platforms. Participants began to modify their digital marketing strategies by uploading content more frequently and producing higher-quality media. In conclusion, this training successfully improved the participants' skills in digital promotion, creating long-term opportunities to enhance the competitiveness of local fishery products through the effective use of digital media.